The Financial crisis and developing countries : a global multidisciplinary perspective - Bergeijk, Peter A. G. van; Haan, Arjan de; Van der Hoeven, Rolph (Cheltenham Edward Elgar Publishing Ltd.)
Summar from British Library Caalogue: "The Financial Crisis and Developing Countries is an invaluable discussion and analysis of the regional and country specific impacts of the financial crisis in both emerging markets and developing countries. Using heterodox and mainstream methodologies, the book develops a multidisciplinary perspective on the crisis, showing empirical impacts on the poor and vulnerable. It examines how the crisis continues to change our concepts of development, critically discusses mainstream approaches, and analyses (global) governance responses including of the G20. The contributors critically assess the measures taken to deal with the crisis, and reveal that many elements that have led to crisis (inequality, inappropriate international financial architecture, structural imbalances) have not been dealt with sufficiently, and as a result new crises will continue to emerge. Exploring a global and inter-disciplinary view, this timely book provides accessible information on the impact of the crisis that will prove relevant for students of development studies and international economics. Researchers and policymakers including in foreign and economic affairs, development cooperation, and international institutions interested in understanding the impact of the global economy will also find much to learn from this important book."
Introduction : Crisis? What crisis? For whom? / Peter A.G van Bergeijk, Arjan de Haan and Rolph van der Hoeven - Re-orienting development in uncertain times / Jayati Ghosh - How have poor women and men experienced the global economic crisis : what have we learned? / Duncan Green and Richard King - After the Gold Rush : prospects for Africa, economic recovery and long-term growth / Fantu Cheru - A historical ethnography of recessions : crises in Yogyakarta / Ben White - Chinese savings gluts or northern financialisation? The ideological expediency of crisis narratives / Andrew Martin Fischer - Short and long run macroeconomic effects of Keynesian trade policies in the presence of debt servicing / Syed Mansoob Murshed - FDI volatility and development / Irene van Staveren - Financial globalization, current crisis and labour in developing countries / Rolph van der Hoeven - Impact of the global crises (financial, economic and food) : the case of microfinance in Latin America / Reynaldo Marconi and Harry Clemens - Crisis, employment and poverty in the Middle East and North Africa / Mahmood Messkoub - Crisis and exclusionary growth in Europe's 'East' / Max Spoor - The crisis in South Asia : from jobless growth to jobless slump? / Karin Astrid Siegmann - Diamonds are for never : the economic crisis and the diamond polishing industry in India / Astha Kapoor- Defending vulnerable workers in South Africa after the crisis : what role for COSATU? / Freek B. Schiphorst - How China managed the impact of the financial crisis : globalization and public policy responses in an emerging economy / Arjan de Haan and Sen Gong - Thailand from crisis to crisis : do we ever learn? / Karel Jansen - The global economic crisis and the future of globalization / Rob Vos.
Based on contributions to three international scientific events including a conference, workshop and CERES summer school.
Includes bibliogrpahical references (p. 286-313) and index.
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; DEVELOPING COUNTRIES